Abnormal lending and risk in Swedish financial institutions. Issue 4 (12th November 2018) - Papadamou, Stephanos; Philippas, Dionisis; Firas, Batnini; Ntitoras, Thomas
Abstract : Purpose: This paper aims to examine the relationship between abnormal loan growth and risk in Swedish financial institutions by type and borrower using three indicators as proxies for risks related to loan losses, the ratio of interest income to total loans and solvency perspectives. Design/methodology/approach: Using a large sample of different types of Swedish financial institutions, this paper uses a panel framework to examine the relationships between abnormal loan growth rates and loan losses, interest income as a percentage of total loans, changes in the equity to assets ratio and changes in z-score. Findings: The findings show two important points of evidence. First, abnormal lending to retail customers increases loan losses and interest income in relation to total loans. Second, abnormal lending to other credit institutions decreases loan losses and significantly changes the capital structure by increasing the reliance on debt funding and significantly improves the z-score measure. Research limitations/implications: The findings provide useful implications for the management of loan portfolios for a wide range of Swedish financial institutions, identifying two components: abnormal lending to households may increase loan losses and increase interest income in relation to total loans, and excessive lending to other credit institutions may reduce solvency risk and allow more debt financing for the financial institution. Originality/value: This is the first study to use a panel framework in analyzing the behavior of different types of Swedish financial institutions in relation to loans granted to retail customers and other credit institutions.